1995
DOI: 10.1677/joe.0.1470095
|View full text |Cite
|
Sign up to set email alerts
|

Effect of octreotide on experimental diabetic renal and glomerular growth: importance of early intervention

Abstract: IGF-I acts as a renotropic factor in early streptozotocin-induced diabetes. Somatostatin analogue (octreotide) treatment initiated at the onset of diabetes prevents kidney IGF-I accumulation and renal growth. Seven days of octreotide treatment initiated after 3, 5, 7 or 9 days of untreated diabetes was investigated. Diabetic renal hypertrophy was followed by renal hyperplasia. Compared with placebo-treated diabetic rats, the earliest octreotide intervention was followed by a greater reduction in renal growth c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…In the diabetic rat models, only a transient early increase in kidney IGF-I levels is observed (Flyvbjerg et al 1989, Grønbaek et al 1996. Further, the kidney IGF-I increase seems to be important as postponement of octreotide treatment to 3-9 days after the induction of diabetes is followed by less significant inhibition of renal and glomerular growth (Grønbaek et al 1995b). In the present study, octreotide treatment significantly reduced kidney IGF-I levels after 7 days, but not by the end of the study, and elevated IGF-I levels were observed in both diabetic groups compared with controls by day 14.…”
Section: Discussionsupporting
confidence: 41%
“…In the diabetic rat models, only a transient early increase in kidney IGF-I levels is observed (Flyvbjerg et al 1989, Grønbaek et al 1996. Further, the kidney IGF-I increase seems to be important as postponement of octreotide treatment to 3-9 days after the induction of diabetes is followed by less significant inhibition of renal and glomerular growth (Grønbaek et al 1995b). In the present study, octreotide treatment significantly reduced kidney IGF-I levels after 7 days, but not by the end of the study, and elevated IGF-I levels were observed in both diabetic groups compared with controls by day 14.…”
Section: Discussionsupporting
confidence: 41%